International Surrogacy Arrangements - Perspectives on International Regulation - Alihodžić, Jasmina; Duraković, Anita (Medicine, Law & Society, 2020)
Although more than 30 years have passed since the birth of the first surrogate baby, surrogacy motherhood as a form of ART is still one of the most controversial issues that reflect moral, ethical, cultural, psychological, medical, economic and legal dilemmas. The juxtaposition of legal solutions at the national level has given rise to discussions on the optimal solutions for regulating model international surrogacy arrangements. Given the current social and political climate, the authors of this paper advocate for the reform of international adoption procedures as opposed to passing a new convention, in a way that respective provisions of international adoption convention should be adapted to capture the effects of international surrogacy arrangements - recognition of legal parentage, provided that it is in the best interests of the child, and that there is a biological link between the child and at least one intended parent.
Keywords: international surrogacy arrangements; international regulation; reform of international adoption procedure; recognition of legal parentage; the best interest of the child